Embedding green environment to increase indoor air quality in academic library - Wan Azib, Wan Nor Hazimah; Idris, Zaila; Ismail, Hadhifah Fadhlina; Mohd Shukry, Amira Idayu (Universiti Teknologi MARA, Kedah, 2017)
Inadequacy of oxygen was common problem addressed in closed areas such as library and classroom. This prototype layout has identified the suitable plant to be located inside academic library in Malaysia using ten species of natural plant as suggested by NASA to improve indoor air quality of a library building. Two species out of ten plants namely Chinese Evergreen Aglaonema and Calla Lilies was selected due to cost and pleasant color that best suited to the corporate image of the identified universities which is significance to the management. The level of current indoor air quality is measured using an IAQ meter device Anemometer which is conducted by DOSH officer. The level of indoor air quality was then recalculated after the placement of plants to measure the differences. This layout was expected to be as a useful tools for a newly design library as well as others confined areas that is proven to increase the health level and mental capacity of building occupants. which is conducted by DOSH officer. The level of indoor air quality was then recalculated after the placement of plants to measure the differences. This layout was expected to be as a useful tools for a newly design library as well as others confined areas that is proven to increase the health level and mental capacity of building occupants. The technique of using two identified species of plants which are Chinese Evergreen Aglaoenma and Calla Lilies as a main agent of improving indoor air quality levels in the selected academic library was the novelty and uniqueness of this project. The choice was made due to relevancy with cost and adequate usefulness of color to match with universities corporate image which has 2 in 1 functions.